Quality analysis and health effects of green plum and Cordyceps militaris fermented wine - ZHENG Taiji, SHEN Yuanyuan, WANG Baozhong, ZHU Hailiang, ZHAO Weimin, ZHANG Ying, WANG Zhongchang (Zhongguo niangzao)
A new type of green plum and Cordyceps militaris fermented wine was prepared, its physicochemical indexes, alcohol content, sensory score, total phenols, total flavonoids, amino acids, minerals, and volatile aroma components were detected and analyzed, and its antioxidant, hypolipidemic and hypoglycemic abilities in vitro, as well as its inhibitory effect on the proliferation of human hepatocellular carcinoma cells (HepG2) and colorectal carcinomas cells (HCT116) were evaluated. Results showed that the alcohol content of green plum and C. militaris fermented wine was 12.65%vol, the sensory score was 93.02 points, and the physicochemical and microbial indexes met the "green food fruit wine" standards. The wine was rich in 6 minerals (potassium, calcium, magnesium, zinc, copper, iron) and 17 amino acids, and a total of 37 volatile components were detected. The scavenging rates on ABTS+ and DPPH free radicals were (96.58±1.19)% and (94.15±0.24)%, exhibited a strong antioxidant effect. The binding rate of green plum and C. militaris fermented wine freeze-dried powder solution to sodium taurocholate was (65.50±1.24)% and the inhibition rate of α-glucosidase was (83.52±0.23)%, indicating that it could effectively reduce blood lipids and blood glucose. The proliferation inhibition rates on the HepG2 and HCT116 cancer cells were (83.16±0.54)% and (75.94±2.18)%, showing a good inhibitory effect. In summary, the green plum and C. militaris fermented wine was a functional drink with rich nutrients and multiple health effects.